2011
DOI: 10.1016/j.visres.2010.10.025
|View full text |Cite
|
Sign up to set email alerts
|

A mammalian melanopsin in the retina of a fresh water turtle, the red-eared slider (Trachemys scripta elegans)

Abstract: A mammalian-like melanopsin (Opn4m) has been found in all major vertebrate classes except reptile. Since the pupillary light reflex (PLR) of the fresh water turtle takes between 5 and 10 min to achieve maximum constriction, and since photosensitive retinal ganglion cells (ipRGCs) in mammals use Opn4m to control their slow sustained pupil responses, we hypothesized that a Opn4m homolog exists in the retina of the turtle. To identify its presence, retinal tissue was dissected from seven turtles, and total RNA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
5
0
4
Order By: Relevance
“…However, direct stimulation of the efferent pathway results in much faster pupillary constriction (Dearworth et al, 2009), suggesting the cause of the sluggish PLR of turtles is to be found within the afferent part of the reflex arc. In the turtle, pupillary constriction may, for example, be more reliant than mammals on melanopsin-containing ipRGCs, whose dynamics are slow (Dearworth et al, 2011; Section 5.1).…”
Section: Innervation Of the Sphinctermentioning
confidence: 99%
“…However, direct stimulation of the efferent pathway results in much faster pupillary constriction (Dearworth et al, 2009), suggesting the cause of the sluggish PLR of turtles is to be found within the afferent part of the reflex arc. In the turtle, pupillary constriction may, for example, be more reliant than mammals on melanopsin-containing ipRGCs, whose dynamics are slow (Dearworth et al, 2011; Section 5.1).…”
Section: Innervation Of the Sphinctermentioning
confidence: 99%
“…Nonetheless, parietalectomy affects melatonin biosynthesis by the pineal gland, and the circadian rhythm in iguanid ( Sceloporus occidentalis; Bethea & Walker, ) and scincid ( Trachydosaurus rugosus ; Firth & Kennaway, ) lizards, reflecting a neuronal connection between the parietal eye and pineal gland. The fact that melanopsin is absent from the reptilian pineal complex (Dearworth et al., ; Frigato, Vallone, Bertolucci, & Foulkes, ; Figure d), suggests that either a melanopsin‐activated eye‐pineal gland neural circuit or other photopigments within the pineal complex regulate melatonin secretion. Data from zebrafish support the idea that photopigments other than melanopsin regulate melatonin secretion.…”
Section: Seeing the Light: Melanopsin Expression And The Evolutionarymentioning
confidence: 99%
“…This species is also used as a laboratory animal model for basic investigation in vision, particularly for pupillary light reflex and retinal research. [1][2][3][4] Normal mean intraocular pressure (IOP) values have been reported for a number of healthy, conscious and chemically restrained exotic and wild animal species. [5][6][7][8][9] While limited information is available on IOP in some terrestrial reptile species, 10 in aquatic freshwater turtles, such as red-eared slider turtles, normal IOP values have not been reported [11][12][13][14] and ocular anatomy and normal ophthalmic reference data for this species are scarce.…”
Section: Introductionmentioning
confidence: 99%